2020
DOI: 10.1242/dmm.042853
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PRSS56 function leads to ocular angle defects and increased susceptibility to high intraocular pressure

Abstract: Glaucoma is a leading cause of blindness affecting up to million people worldwide. High intraocular pressure (IOP) is a major risk factor for glaucoma. Inefficient aqueous humor (AqH) outflow resulting from structural or functional alterations in ocular drainage tissues are well established to cause high IOP, but the genes and pathways involved are poorly understood. We previously demonstrated that mutations in the gene encoding the serine protease PRSS56 induces ocular angle-closure and high IOP in mice and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Several mouse models relevant to early onset developmental forms of glaucoma have been described (Akula et al, 2020;Chang et al, 2001;Chen and Gage, 2016;Ishibashi et al, 1999;Iwao et al, 2009;Kroeber et al, 2010;Labelle-Dumais et al, 2020;Lachke et al, 2011;Smith et al, 2000;Thomson et al, 2017;Tolman et al, 2021). Among them, many studies have focused on phenotypes of the anterior segment and there have been relatively few in depth studies of RGC damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several mouse models relevant to early onset developmental forms of glaucoma have been described (Akula et al, 2020;Chang et al, 2001;Chen and Gage, 2016;Ishibashi et al, 1999;Iwao et al, 2009;Kroeber et al, 2010;Labelle-Dumais et al, 2020;Lachke et al, 2011;Smith et al, 2000;Thomson et al, 2017;Tolman et al, 2021). Among them, many studies have focused on phenotypes of the anterior segment and there have been relatively few in depth studies of RGC damage.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were embedded in glycol methacrylate, and serial sagittal sections (2 μm) passing through the optic nerve were cut and stained with hematoxylin and eosin (H&E). Ten similarly spaced sections corresponding to the peripheral, mid- peripheral and central regions (passing through the optic nerve) of the eye were evaluated 81 . Both angles of a section were considered for evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Ten similarly spaced sections corresponding to the peripheral, mid-peripheral and central regions (passing through the optic nerve) of the eye were evaluated 81 . Both angles of a section were considered for evaluation.…”
Section: Ocular Angle Assessmentmentioning
confidence: 99%
“… 204 Furthermore, Prss56 -/- mice have been recently shown to exhibit ocular angle defects and increased risk of high IOP. 205 The study suggested a critical role for PRSS56 in the development and maintenance of ocular drainage tissues and IOP homeostasis. 205 …”
Section: Animal-model Studies In Pacgmentioning
confidence: 98%
“… 205 The study suggested a critical role for PRSS56 in the development and maintenance of ocular drainage tissues and IOP homeostasis. 205 …”
Section: Animal-model Studies In Pacgmentioning
confidence: 98%